Education in India during the British Period (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Education in India during the British period went through a deep and uneven transformation. Pre-colonial learning had multiple streams, including pathshalas and maktabs for basic instruction, madrasas for higher Islamic learning, and Sanskrit tols for advanced Hindu scholarship, along with apprenticeship-based training for crafts and professions. British rule reshaped these systems by introducing new administrative priorities, Western curricula, printed textbooks, and examinations, while also encouraging English as a language of power. The shift was not sudden; it unfolded through policy milestones such as the Charter Act of 1813, Macaulay’s Minute (1835), Wood’s Dispatch (1854), the establishment of universities (1857), and later commissions that tried to address access and quality. While colonial education expanded schooling and created a new class of educated Indians who would later drive social reform and nationalism, it also produced lasting problems such as limited mass literacy, social exclusion, and an exam-centered system geared toward clerical employment. This paper examines major policies, institutions, social impacts, and criticisms of colonial education, and it highlights how the British period left a complex legacy that continued to shape India’s educational priorities after independence.